Changes of adenosine deaminase activity in serum and saliva around parturition in sows with and without postpartum dysgalactia syndrome - Marianne Kaiser (BMC, 2021)
Abstract Background Postpartum dysgalactia syndrome (PDS) is associated with a significantly higher activation of the inflammatory and stress response at parturition than in the healthy sow. Therefore, reliable and possibly non-invasive biomarkers for substantial increases of inflammation are searched to support the PDS diagnosis. This report studies the possible changes of the inflammatory marker enzyme adenosine deaminase (ADA) in serum and saliva of 38 PDS positive sows (PDS+) and 38 healthy sows (PDS-). Sampling was performed every 24 h from 60 h before to 36 h after parturition. Isoenzyme 1 (ADA1) and isoenzyme 2 (ADA2), as well as total ADA (tADA), were measured and their statistical association with several serum and saliva biomarkers of inflammation and stress was investigated. Results Compared to a baseline (60 to 36h prepartum), salivary activities of ADA1, ADA2 and tADA increased significantly over time in both PDS+ and PDS- sows, reaching their peaks after parturition. In serum from PDS- sows, no changes were observed over time in either ADA1, ADA2 or tADA. In PDS+ sows, serum ADA2 activity decreased temporarily after parturition followed by a significant increase compared to baseline. ADA1, ADA2 and tADA were all significantly associated with several inflammatory biomarkers and ADA1 in serum was associated with serum cortisol. Although serum activity was higher in PDS+ than in PDS- sows, the differences were not statistically significant. Further, no difference was noted between the groups in the analyses of saliva. Conclusions Salivary ADA1 and ADA2 increased in all sows after parturition, potentially as a response to the postpartum inflammation. However, no difference in the activity of ADA1, ADA2 and tADA were found between PDS+ and PDS- sows indicating inability to diagnose PDS under the conditions described in this report.